H3K36 methyltransferase NSD1 is essential for normal B1 and B2 cell development and germinal center formation - Zhai, Sulan; Cao, Min; Zhou, Han; Zhu, Huamin; Xu, Tongchang; Wang, Yuliang; Wang, Xiaoming; Cai, Zhenming (Frontiers in Immunology, 2022)
B cells, which consist of two well-defined populations: B1 and B2 cells, which can produce antibodies that are essential for host protection against infections, through virus neutralization, opsonization and antibody-dependent cellular cytotoxicity. Epigenetic modifications, such as DNA methylation and histone modification could regulate immune cell differentiation and functions. In this study, we found a significant reduction of GC response in the B cell specific knockout of H3K36 methyltransferase NSD1 (Mb1-Cre+ NSD1fl/fl, NSD1B KO) mice compared with the wildtype control (Mb1-Cre+ NSD1+/+, NSD1B WT). We also demonstrated reduced production of high-affinity antibody, but increased production of low-affinity antibody in the NSD1B KO mice. Further analysis revealed that loss of NSD1 promoted the development of B1 cells by increasing the expression of Rap1b and Arid3a. In conclusion, our data suggest that NSD1 plays an important role in regulation the development of B1 and B2 cells, and the process of germinal center formation and high-affinity antibody production.